Use of perfusion bioreactors and large animal models for long bone tissue engineering - Gardel, Leandro S. (2014)
Tissue engineering and regenerative medicine (TERM) strategies for generation of new bone tissue includes the combined use of autologous or heterologous mesenchymal stem cells (MSC) and three-dimensional (3D) scaffold materials serving as structural support for the cells, that develop into tissue-like substitutes under appropriate in vitro culture conditions. This approach is very important due to the limitations and risks associated with autologous, as well as allogenic bone grafiting procedures currently used. However, the cultivation of osteoprogenitor cells in 3D scaffolds presents several challenges, such as the efficient transport of nutrient and oxygen and removal of waste products from the cells in the interior of the scaffold. In this context, perfusion bioreactor systems are key components for bone TERM, as many recent studies have shown that such systems can provide dynamic environments with enhanced diffusion of nutrients and therefore, perfusion can be used to generate grafts of clinically relevant sizes and shapes. Nevertheless, to determine whether a developed tissue-like substitute conforms to the requirements of biocompatibility, mechanical stability and safety, it must undergo rigorous testing both in vitro and in vivo. Results from in vitro studies can be difficult to extrapolate to the in vivo situation, and for this reason, the use of animal models is often an essential step in the testing of orthopedic implants before clinical use in humans. This review provides an overview of the concepts, advantages, and challenges associated with different types of perfusion bioreactor systems, particularly focusing on systems that may enable the generation of critical size tissue engineered constructs. Furthermore, this review discusses some of the most frequently used animal models, such as sheep and goats, to study the in vivo functionality of bone implant materials, in critical size defects.